Modification level and test of scientific argumentation skill: Development and validity - Riki Perdana; Riwayani Riwayani; Jumadi Jumadi; Dadan Rosana (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study focuses on developing the new level of scientific argumentation skills and new items that are feasible and valid for used. There are 195 science students at Islamic State School 1 (MAN 1) Yogyakarta as participant in this study. Random sampling technique was used from the three schools of Islamis State School (MAN) in Yogyakarta, Indonesia. There are seven experts (3 Professor, 2 teachers, and 2 graduate students) reviewed 14 items for the first phase of this study. For the second phase, 98 students answered 14 questions which each questions contain five point (claim, data, backing, warrant and rebuttal). For the third phase, after choosed the best five 5 questions, We asked the others (97 students) to answer those questions. The modification of the level of scientific argumentation skills indicates the ability of students is still low. At level 1 (claims) there were only 38.9% students, level 2 (data) were 21.6% students, level 3 (warrants) 16.6% students, level 4 (backing) 16.2% while level 5 (rebuttal) is the most difficult, for students’ users only by 4.2%. Based on the findings, the test can measure and show with a separate level of students' scientific argumentation skill in this school.